KESIAPAN MAHASISWA PENDIDIKAN TEKNIK BOGA DALAM PELAKSANAAAN PEMBELAJARAN MATA KULIAH MANAJEMEN USAHA BOGA DI PROGRAM STUDI PENDIDIKAN TEKNIK BOGA PTBB FT UNY - Yuriani Yuriani; Titin Hera Widi Handayani (Faculty of Engineering, Universitas Negeri Yogyakarta, 2012)
ABSTRACTThe objectives of this study are (1) to investigate the implementation of the culinary business management course, (2) to investigate the students’ readiness in preparing culinary business management course, (3) to find out the students’ readiness in the implementation of the culinary business management course, and (4) to find out the obstacles in the learning process of this course. This study was employing descriptive approach in 16 March – 31 October 2012 at Culinary Education Study Program of Faculty of Engineering, Yogyakarta State University. The population was the students of Culinary Education Study Program who joined culinary business management course among the second semester students in the academic year of 2011/ 2012. The sampling technique was using random sampling with the total respondents of 72 students. The data were collected by using interview, questionnaire, and observation while the data were analyzed by using quantitative and qualitative descriptive. The findings revealed that firstly, the implementation of the learning of culinary business management course consisted of the opening preparation of the new business, the managing process, and the assessment that covered active participation, independent task, group work, practice, and final examination with 53% of the students achieved A, 28% of them achieved A- , 17% of them achieved B+, and 4% of them achieved B. Secondly, students’ readiness in implementing the culinary business management course can be categorized as “very high” category with 12.5% and the category of “high” with 87.5%. Thirdly, students’ readiness in the culinary business management course was in the category of “very high” with 16.67% and the category of “high” with 83.33%. Lastly, the obstacles in implementing the learning process of culinary business management were the communication and cooperation among the team, students’ loyalty and discipline, insufficient time of the course, and inadequate facilities and tools.Keywords : students’ readiness, culinary business management